2020
DOI: 10.1101/2020.02.19.956177
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-throughput laboratory evolution and evolutionary constraints inEscherichia coli

Abstract: These authors contributed equally to this work. SUMMARYUnderstanding the constraints that shape the evolution of antibiotic resistance is critical for predicting and controlling drug resistance. Despite its importance, however, a systematic investigation for evolutionary constraints is lacking. Here, we performed a high-throughput laboratory evolution of Escherichia coli under the addition of 95 antibacterial chemicals and quantified the transcriptome, resistance, and genomic profiles for the evolved strains. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
2
4
0
Order By: Relevance
“…The detection of a mutation in Rv2864c in the meropenem-resistant Mtb isolates in our study is in accordance with these observations and further supported by reports of increased cefotaxime sensitivity in a Mtb mutant generated through Rv2864c disruption and by CRISPR interference studies on Mycobacterium abscessus orthologue gene MAB_3167c (Wivagg et al, 2016;Akusobi et al, 2022). Maeda et al (2021) additionally report in their meropenemselected mutants a non-synonymous mutation in the coding sequence of MSMEG_6319 and an intergenic variant upstream MSMEG_6406 (AT701_RS31385), orthologue of Rv3811 and which encodes a putative N-acetylmuramoyl-l-alanine amidase. We did not observe the two latter features, but two of our meropenem-exposed mutants alternatively displayed a mutation 11 bp upstream the TSS of MSMEG_6317, adjacent to MSMEG_6319.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The detection of a mutation in Rv2864c in the meropenem-resistant Mtb isolates in our study is in accordance with these observations and further supported by reports of increased cefotaxime sensitivity in a Mtb mutant generated through Rv2864c disruption and by CRISPR interference studies on Mycobacterium abscessus orthologue gene MAB_3167c (Wivagg et al, 2016;Akusobi et al, 2022). Maeda et al (2021) additionally report in their meropenemselected mutants a non-synonymous mutation in the coding sequence of MSMEG_6319 and an intergenic variant upstream MSMEG_6406 (AT701_RS31385), orthologue of Rv3811 and which encodes a putative N-acetylmuramoyl-l-alanine amidase. We did not observe the two latter features, but two of our meropenem-exposed mutants alternatively displayed a mutation 11 bp upstream the TSS of MSMEG_6317, adjacent to MSMEG_6319.…”
Section: Discussionsupporting
confidence: 92%
“…In conclusion, our study outputs imply that mycobacterial resistance to beta-lactams may not be as simplistic as once thought. Confirmation of mutations in Rv2864c and upstream MSMEG_6319 in mutants isolated with meropenem, corroborated previous descriptions of the involvement of the Msm gene in resistance to this carbapenem (Maeda et al, 2021). This is also in 10.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Several mutations that sensitized K. pneumoniae to ruthenium red, such as uvrD and recCG, have been shown to render bacteria more susceptible to DNA-damaging antibiotics such as ciprofloxacin (Tamae et al, 2008), suggesting that ruthenium red treatment leads to damaged DNA. Indeed, ruthenium red has been shown to bind DNA in vitro (Karpel et al, 1981), and a recent report showed that recA mutants of E. coli were more susceptible to this compound (Maeda et al, 2019). Ruthenium red has also been shown to modulate the polymerization of FtsZ in vitro, which plays an important role in cell division and interacts with FtsK (Grenga et al, 2008;Santra et al, 2004).…”
Section: K Pneumoniae Is Uniquely Susceptible To Dna Damage By Ruthenium Red When Grown In Serummentioning
confidence: 99%
“…In contrast to the method of agar-based selection for laboratory evolution against antibiotics (Maeda et al, 2021) or induced by high-concentration drugs (Zhao et al, 2014), the strategy of a continuous drug concentration gradient can better simulate the accumulation of drugs in the human body. Determination of the MIC value of 14 anti-TB drugs showed that laboratory-induced mono-EMB drug-resistant strains were successfully obtained (Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 99%